Interaction of Cleat-Matrix on Coal Permeability from Experimental Observations and Numerical Analysis - Chunguang Wang; Yuxiao Zang; Linsen Wang; Zhongwei Chen; Guanglei Cui; Kunkun Fan; Weitao Liu (Geofluids)
Gas transport through porous coal contains gas laminar flow in the cleat network and gas adsorption/diffusion in the matrix block. Since permeable capacity of the cleat is greater than that of the matrix, change of the matrix pressure readily lags behind change in the cleat pressure. Such unsynchronized pressure changes can result in a complex compatible deformation of a cleat-matrix system, significantly affecting the coal permeability. In this paper, we investigated the cleat-matrix interaction on coal permeability by using a modified pressure pulse decay method integrated with numerical analysis. The experimental results indicate that the bulk volume of the coal sample rapidly expanded at the beginning of gas injection, and then the volume expansion rate of the coal sample slowed down as the downstream pressure of the coal sample gradually equilibrated with the upstream pressure. During this process, the coal permeability was observed to gradually decrease with time. Numerical analysis results indicate that gas transport from the cleat to the matrix can attenuate the differential pressure between the cleat and the matrix. A smaller ratio of initial matrix permeability to initial cleat permeability can prolong decay duration of the differential pressure inside the cleat-matrix system. Although the coal sample is subjected to a stress-controlled condition, the coal permeability response to gas diffusion is closer to the case using a constant volume boundary. The dynamic change of coal permeability is significantly affected by the cleat-matrix interaction, in cases where the short-term change is mainly attributable to the cleat network and the long-term change is controlled by matrix swelling/shrinkage.